2019
DOI: 10.14639/0392-100x-n0221
|View full text |Cite
|
Sign up to set email alerts
|

Time as a factor during endoscopic assessment of swallowing: relevance in defining the score and severity of swallowing disorders

Abstract: Il tempo come fattore durante la valutazione endoscopica della deglutizione: la sua rilevanza nel definire il punteggio e la gravità dei disturbi della deglutizione

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…This is in line with previous data in the literature [20]. It is worth to be mentioned that recent data in the literature have confirmed a correlation with residue and false routes as main indicators of dysphagia [16,21,22], with a significant correlation of the sub-scale "site" 3-4 of the p-score with, respectively, the scores 2-5 and 6-8 of the PAS scale [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previous data in the literature [20]. It is worth to be mentioned that recent data in the literature have confirmed a correlation with residue and false routes as main indicators of dysphagia [16,21,22], with a significant correlation of the sub-scale "site" 3-4 of the p-score with, respectively, the scores 2-5 and 6-8 of the PAS scale [16].…”
Section: Discussionsupporting
confidence: 92%
“…After each consistency the severity of dysphagia, in terms of false route and residue, was defined applying the pooling score (p-score) and applying the Sensation, Collaboration and Age score (p-SCA score) [14] (Table 1). The p-score has been documented to have good predictive ability on penetration and aspiration when compared with the penetration aspiration scale (PAS scale) [15,16].…”
Section: Protocolmentioning
confidence: 99%
“…Towards this objective, it is important to evaluate the scores from questionnaires not in absolute terms, but in relation to the clinical background. Moreover, the risk in underestimating dysphagia may be reduced by associating physical and instrumental assessment to characterise the abnormalities in the oral and pharyngeal stages of swallowing 34 .…”
Section: Diadochokinesismentioning
confidence: 99%
“… 3. Functional assessment of swallowing Farneti et al, 2019 41 Different etiologies: PD, vascular dementia, stroke, TBI. 16 adults (11 men) Own protocol with consistencies based on the global initiative FEES associated with penetration-aspiration scale, FOIS, and DOSS 1.…”
Section: Resultsmentioning
confidence: 99%
“…Shapira-Galitz et al 30 suggested a possibility of assessment bias at the time when the researchers needed to read the questionnaire for patients over the phone. D’Ottaviano et al, 31 Leder et al, 22 Mandysova et al, 21 Marian et al, 32 Gozzer et al, 33 Imaizumi et al, 34 Schröder et al, 35 Pilz et al, 36 Somasundaram et al, 37 Souza et al, 38 Souza et al, 39 Umay et al, 40 and Farneti et al 41 did not describe the bias assessment.…”
Section: Resultsmentioning
confidence: 99%